Sikap Siswa Terhadap Guru dan Faktor yang Mempengaruhinya - Yanti, Resi; Kubuwono, Hameng; Ristianti, Dina Hajja (JOEAI (Journal of Education and Instruction), 2020)
This study aims to find out the attitude of students towards teachers and the factors that influence them in SMPN 4 Bermani Ilir. This research is a field research with qualitative approach. Data collection techniques used in this research include observation, interviews and documentation. Data analysis techniques in this study include data reduction, data presentation and conclusions. The results of the study obtained information that students should maintain the boundaries between themselves and their teachers, by maintaining a polite attitude, manners, not testing the ability of teachers, and so on. As a student must realize that the teacher is a figure that must be respected and obeyed if it does not deviate from the teachings of islam. With this, teachers also hope that students can follow their attitudes so that students can develop care by listening, politeness, obedience and honor. Factors that influence students' attitude towards their teachers in school are internal factors and external factors. In conclusion, students' attitude towards teachers should maintain the boundaries between students and teachers, maintain attitudes and exemplify teachers by maintaining politeness, compliance and respect for teachers. Keywords: Influencing Factors, Student Attitudes, Attitudes Towards Teachers